DEVELOPMENT OF A SUSTAINABILITY STRATEGY FOR A ROAD CONSTRUCTION COMPANY IN LATVIA (ENVIRONMENT. TECHNOLOGY. RESOURCES. Proceedings of the International Scientific and Practical Conference, 2025)
The Corporate Sustainability Reporting Directive (CSRD) entered into force on 5 January 2023. This new directive updates the rules on the social and environmental information that companies must report. Companies covered by the CSRD will be required to report in accordance with the European Sustainability Reporting Standards (ESRS). The unclear direction of the industry's development, unstable and unpredictable funding, limited innovation capacity due to regulatory enactments and various customer-created regulations are significant limitations for future plans. All these challenges, supplemented by the principle of the lowest price, complicate and make it difficult to develop new sustainable development strategies. While the selection criterion is the lowest price, large-scale sustainable innovations can put the company in an uncompetitive market position. Road construction companies need to develop a sustainability strategy that both complies with the new regulatory framework, and is in line with the market reality of the industry, and minimizes future risks that may arise from specifying sustainability goals and principles. A sustainability strategy for the road construction company has been developed. This strategy aims to enhance the company's competitiveness by reducing production costs and minimizing environmental impact. It ensures compliance with future sustainability requirements and mitigates risks associated with the loss of competitiveness. The strategy also incorporates the development of management skills necessary for the successful and efficient implementation of strategic directions and for the further development or adjustment of the sustainability strategy in response to policy changes.